DNA recovery of a gallstone in an action for damages. (December 2015) - Bozzo, W.R.; Carini, G.; Pilili, J.P.; Mirson, D.J.; Lojo, M.M.
Abstract: In the context of a civil action for medical mala praxis a dry gallstone, a gallstone immersed in formalin and a gallbladder in the same preservative were submitted to our lab in order to analyze the identity of the donor. A blood sample of the victim was sent as reference. The dry gallstone showed the appearance of an irregular dark brown stone. Chemical analysis revealed that it was composed mainly of cholesterol. No DNA profiles were recovered from the samples immersed in formalin whereas the dry gallstone rendered a full DNA profile only from samples collected by surface scraping. A female genetic profile that did not match the victim was obtained. Although a gallstone is an unusual sample source, in this case the DNA analysis provided important evidence in solving the dispute.